Hypoxia preconditioned MSC exosomes attenuate high-altitude cerebral edema via the miR-125a-5p/RTEF-1 axis to protect vascular endothelial cells - Jia-Chen Zuo; Jun Liang; Nan Hu; Bin Yao; Qi-Jian Zhang; Xiao-Li Zeng; Ling-Jie Zhang; Xu Zhang; Zhe-Han Chang; Chong Chen; Xin-Jian Yan; Wen-Wei Shao; et al. (Bioactive Materials)
Vasogenic edema, caused by the disruption of the blood-brain barrier (BBB), is a significant pathological factor in high-altitude cerebral edema (HACE). Due to the rapid progression and high mortality rate of HACE, prophylactic treatment is important. Mesenchymal stem cell exosomes (MSC-EXO) are increasingly being used in tissue injury repair, and research suggests that appropriate conditioning can enhance the targeted efficacy of exosome therapy. Our in vitro experiments revealed that hypoxia preconditioned MSC-EXO (H-EXO) significantly outperformed normoxic MSC-EXO (N-EXO) in multiple protective aspects. Specifically, H-EXO demonstrated enhanced capacity to mitigate hypoxia-induced aberrant angiogenesis, maintain vascular endothelial cell viability, and suppress ROS accumulation and apoptotic signaling under hypoxic stress. Mechanistic investigation identified miR-125a-5p cargo in H-EXO as a key mediator of RTEF-1 targeted inhibition during hypoxic exposure. In corresponding in vivo studies, H-EXO administration effectively attenuated HACE-induced pathological angiogenesis while maintaining crucial vascular homeostasis markers. The therapeutic effects manifested through three principal aspects: 1) downregulation of RTEF-1/VEGF hyperexpression, 2) modulation of VE-cadherin, SMA, and PDGFRα + β expression to preserve BBB integrity, and 3) concurrent protection of neurovascular functions against HACE-induced damage. This investigation elucidates the miR-125a-5p/RTEF-1 axis as the central mechanism through which hypoxic preconditioning enhances MSC-EXO's endothelial protective properties. Our findings establish H-EXO's multimodal therapeutic potential, demonstrating its capacity to simultaneously inhibit pathological angiogenesis, restore BBB function, and protect neural tissue under hypoxic stress conditions. The study elucidates key mechanisms underlying clinical prevention and management of HACE by delineating H-EXO's preventive mechanisms against hypoxia-induced cerebrovascular injury.